THE INSTITUTE OF PLEA BARGAINING IN GEORGIA - David Managadze; Nino Tsikhiseli (European Scientific Journal, ESJ, 2014)
Since 2004, a completely new institution for the legal system of Georgia was introduced and actively used in the criminal law on the legislative level, which has changed the traditional procedural course of reviewing criminal cases. This institution is plea bargaining i.e. the bargaining between the prosecution and defence when it is possible the court to reach the verdict without reviewing the case thoroughly. In the article are reviewed new statutes of the Criminal Procedural Code of Georgia as well as the statistical analysis of jurisprudence. Special emphasis is made on the Institute of plea agreement as one of the most significant changes in the criminal proceedings.